Killing two birds with one stone: a chemically plausible scheme for linked nucleic acid replication and coded peptide synthesis - Sutherland, J; Blackburn, J (Elsevier, 1997)
To understand how life began, we must explain the origins of nucleic acid replication and genetically coded peptide synthesis. Neither of these is easy to explain individually; here, we propose a chemically plausible scheme for the evolution of a process that simultaneously produced both polymers. Later, two separate machineries could have evolved from the linked process.